The International Olympic Committee-International Paralympic Committee relationship: Past, present, and future - Legg, D.; Fay, T.; Wolff, E.; Hums, M. (Journal of Sport and Social Issues, 2015)
The inclusion of athletes with a disability into the Olympic Games has been a long-standing issue within the Paralympic Movement. This article reviews the history of including athletes with a disability into the Olympic Games using two frameworks, the Critical Change Factors Model (CCFM) and its companion, the Organizational Continuum for the Inclusion of Identity Groups in Sport (OCIIS). The CCFM and OCIIS were developed by Fay, grounded in critical social, principal-agent, and open systems theories. Last, the authors identify five future scenarios noting where they would fit within the two frameworks.